Preliminary examination of the regulatory regime to establish a foundation university in Turkey - Hussin, Rohayati; Syed Abdul Kader, Sharifah Zubaidah; Yaakub, Noor Inayah; Abdul Rashid, Rusnadewi; Abd Malib, Marziana (Allied Business Academies, 2018)
The foundation and educational systems in Turkey experienced major reforms after the establishment of the Turkish Republic. The Civil Code and Foundation Law which governed both systems were unified under the Foundation Law 2008 for the betterment of both systems. Under this new unified law, a foundation can form a university provided certain procedural requirements are satisfied. Hence, the main objective of this article is to examine the procedural requirements to establlish a Foundation University. By applying the doctrinal approach, this study reviews several past studies and related laws. Semi-structured interviews were conducted with several Turkish respondents in order to clearly examine the topic studied. Content analysis is used to analyse the data obtained. Finally, this study aims to promote a robust international benchmark for waqf (foundation) to be practiced in universities, including in Malaysia.